2008
DOI: 10.1186/1743-422x-5-58
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of cidofovir resistant vaccinia viruses

Abstract: Background: The emergence of drug resistant viruses, together with the possibility of increased virulence, is an important concern in the development of new antiviral compounds. Cidofovir (CDV) is a phosphonate nucleotide that is approved for use against cytomegalovirus retinitis and for the emergency treatment of smallpox or complications following vaccination. One mode of action for CDV has been demonstrated to be the inhibition of the viral DNA polymerase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 20 publications
1
45
1
Order By: Relevance
“…A recent study by Becker et al has shown that VACVs encoding only the A314V substitution are sevenfold more resistant to HPMPC than wild-type VACV; however, these viruses grow poorly in culture (5), unlike our VACV encoding the A314T substitution, which replicated as well as wild-type virus in culture (2). These results suggest that while both substitutions confer similar levels of resistance, viruses encoding the A314T substitution are likely more fit for replication in culture, although a consistent finding among these studies is that HPMPC R viruses were highly attenuated in their virulence in mouse models (2,5). Our previous study also identified an alanine-to-valine substitution at position 684 in the putative polymerase domain of our HPMPC R VACV DNA polymerase genes (2).…”
Section: Times In Medium Containing An Escalating Dose Of (S)-1-[3-hycontrasting
confidence: 44%
See 2 more Smart Citations
“…A recent study by Becker et al has shown that VACVs encoding only the A314V substitution are sevenfold more resistant to HPMPC than wild-type VACV; however, these viruses grow poorly in culture (5), unlike our VACV encoding the A314T substitution, which replicated as well as wild-type virus in culture (2). These results suggest that while both substitutions confer similar levels of resistance, viruses encoding the A314T substitution are likely more fit for replication in culture, although a consistent finding among these studies is that HPMPC R viruses were highly attenuated in their virulence in mouse models (2,5). Our previous study also identified an alanine-to-valine substitution at position 684 in the putative polymerase domain of our HPMPC R VACV DNA polymerase genes (2).…”
Section: Times In Medium Containing An Escalating Dose Of (S)-1-[3-hycontrasting
confidence: 44%
“…Interestingly, three separate studies found that the passage of VACV in the presence of HPMPC leads to the selection of virus encoding either an alanine-tothreonine (2) or alanine-to-valine substitution at position 314 in the viral DNA polymerase (5,33). Our previous study clearly showed through marker rescue experiments that the A314T substitution could confer an approximately fivefold increase in HPMPC resistance in VACV compared to wild-type virus (2).…”
Section: Times In Medium Containing An Escalating Dose Of (S)-1-[3-hymentioning
confidence: 97%
See 1 more Smart Citation
“…Several in vitro studies with purified DNA polymerase of human cytomegalovirus and VACV (33,34,55), and in vivo studies with CDV-resistant viruses (2,5,28,45) have pointed to virus DNA replication as the main target for CDV action. However, no detailed analysis of the effect of CDV on the VACV replicative cycle has ever been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between the effects of CDV on human cytomegalovirus (55) and VACV enzymes have been observed, but overall it has been widely accepted that CDV acts by inhibiting the process of virus DNA replication. Moreover, most CDV-resistant VACV strains contain mutations in the catalytic domain or in the 3Ј-5Ј exonuclease domain of the DNA polymerase (2,5,28,45).…”
mentioning
confidence: 99%